Is healthy behavior contagious: associations of social norms with physical activity and healthy eating - McNaughton Sarah A; Abbott Gavin; Jeffery Robert W; Ball Kylie; Crawford David (BMC, 2010)
Abstract Background Social norms are theoretically hypothesized to influence health-related behaviors such as physical activity and eating behaviors. However, empirical evidence relating social norms to these behaviors, independently of other more commonly-investigated social constructs such as social support, is scarce and findings equivocal, perhaps due to limitations in the ways in which social norms have been conceptualized and assessed. This study investigated associations between clearly-defined social norms and a range of physical activity and eating behaviors amongst women, adjusting for the effects of social support. Methods Self-report survey data about particular physical activity (leisure-time moderate-vigorous activity; volitional walking; cycling for transport) and eating behaviors (fast food, soft drink and fruit and vegetable consumption), and social norms and support for these, were provided by 3,610 women aged 18-46 years living in socioeconomically disadvantaged neighborhoods in Victoria, Australia. Results Results of regression analyses showed that social norms for physical activity and eating behaviors predicted these respective behaviors relatively consistently; these associations generally remained significant after adjustment for social support. Conclusions Acknowledging the cross-sectional study design, these data confirm theoretical accounts of the importance of social norms for physical activity and eating behaviors, and suggest that this is independent from social support. Intervention strategies aimed at promoting physical activity and healthy eating could incorporate strategies aimed at modifying social norms relating to these behaviors.